Water protection in the Baltic Sea and the Chesapeake Bay : institutions, policies and efficiency - Iho, Antti; Ribaudo, Marc; Hyytiäinen, Kari (Elsevier, 2015)
The Baltic Sea and the Chesapeake Bay share many characteristics. Both are shallow, brackish marine areas that suffer from eutrophication. Successful policies targeting point source pollution have lowered nutrient loads in both areas, but achieving the desired marine quality will require further abatement: efforts may be extended to more complicated and expensive pollution sources, notably agricultural nonpoint loads. Despite their ecological similarities, the two watersheds have different histories and institutional settings and have thus adopted different policies. Comparing and contrasting the policies reveal ways to improve the efficiency of each and ways to avoid the path of trial and error. No comparison of the parallel protection efforts, which involve expenditures of hundreds of millions of dol- lars annually, has been carried out to date. The present paper analyzes the policies applied in the two regions, distilling the results into six recommendations for future steps in preserving what are valuable sea areas
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; point source pollution; nonpoint source pollution; nutrient trading; Baltic Sea; Cheaspeake Bay; cost-efficiency